Intertemporal Labor Supply and the Distribution of Family Income - Shaw, Kathryn L. (The Review of Economics and Statistics, 1989)
The earnings of married women have a more equalizing effect on the distribution of lifetime family earnings (or the expected present value of earnings) than on the distribution of annual family earnings, using Panel Study of Income Dynamics longitudinal data. The intertemporal variability of wives' labor supply causes the correlation between the lifetime earnings of husbands and wives to weaken relative to the correlation between their annual incomes, resulting in lower lifetime inequality. The inequality of potential income (full employment earnings) is found to be much greater for lifetime earnings than average annual earnings, based on alternative endogenous wage-hours models. Copyright 1989 by MIT Press.